Securing sensor reports in wireless sensor networks - Pathan, Al-Sakib Khan; Hong, Choong Seon (Springer-Verlag, 2007)
The sensor reports from a wireless sensor network are often used extensively in the decision making process in many systems and applications. Hence, classifying real and false sensor reports is necessary to avoid unwanted results. In this paper, we propose a scheme for securing the sensor reports in a wireless sensor network. We use one-way hash chain and pre-stored shared secret keys to provide data transmission security for the reports that travel from any source node to the base station. To introduce data freshness, our scheme includes an optional key refreshment mechanism which could be applied depending upon the requirement or the application at hand. We present an analysis along with the detailed description of our scheme.